Anthropometric characteristics and body composition of Italian national wrestlers - Zaccagni, L. (European Journal of Sport Science, 2012)
The aim of this study was to examine the anthropometric characteristics and body composition of wrestlers from the Italian national team. The study was carried out on a sample of 23 wrestlers (9 females and 14 males) aged 18-33 years. Various anthropometric measurements were performed (weight, height, sitting height, some girths and skinfold thicknesses) and anthropometric indices calculated (body mass index, cormic index, upper arm muscle area, upper arm fat area, and arm fat index). Body composition was assessed and minimum wrestling weight was determined based on a minimum body fat percentage of 5% for males and 12% for females. We undertook comparisons by sex, wrestling style (for males), and weight category. The comparison between men's and women's wrestling corroborated known differences between the sexes; the comparison between wrestling styles stressed the relevance of the cormic index. The most interesting finding of this study was that no female wrestler competed in a lower weight class than her minimum wrestling weight, even if all of them were heavier than values allowed for their weight class. Five of 14 male wrestlers competed in a weight class lower than their minimum wrestling weight, and all of them, except two, were heavier than the uppermost limit of their weight class.